Forest litterfall and its composition: a new data set of observational data from C hina - Bingrui Jia; Guangsheng Zhou; Zhenzhu Xu (Ecology, 2016)
Knowledge of litterfall production and its allocation is important for understanding nutrient cycling and assessing productivity in forest ecosystems; however, available litterfall datasets are rare in China. Consequently, in the present study, data from published studies (1970–2014) on litterfall and its composition in forest ecosystems in China (excluding Hong Kong, Macao, and Taiwan) were collected, critically reviewed, and incorporated in a comprehensive forest litterfall data set for China. The data set included the following litterfall data: leaves, branches, reproductive parts (flowers and fruits), and miscellaneous. Moreover, associated information was also included, i.e., geographical location (latitude, longitude, altitude, aspect, and slope), climate [mean annual temperature ( MAT ) and mean annual precipitation ( MAP )], stand description (forest type, dominant tree species, stand origin, stand age, mean DBH , mean tree height and stand density), and data collection regime (sample frequency and date, trap size, and number). The data set included 904 entries for 168 study sites, that were distributed in various climate zones with latitudes 18.26°–51.50° N, longitudes 82.25°–129.53° E and altitudes 0–4115 m above sea level (a.s.l.), covering broad climatic gradients (−5.4 to 25.4°C in MAT and 370 to 2800 mm in MAP ). The data can be used to analyze spatio‐temporal dynamics of China's forest litterfall and its allocation, understand nutrient cycling and assess productivity in forest ecosystems. Finally, the data set is freely available for noncommercial scientific applications.